REVIEW OF DEER KED (LIPOPTENA CERVI) ON MOOSE IN SCANDINAVIA WITH IMPLICATIONS FOR NORTH AMERICA - Samuel, Bill; Madslien, Knut; Gonynor-McGuire, Jessica (Lakehead University, 2012)
The deer ked (Lipoptena cervi) is an Old World dipteran ectoparasite of moose (Alces alces) and other Cervidae. It has undergone significant expansion in distribution on moose of Scandinavia in recent decades. This has been accompanied by much published research dealing with the range expansion and possible factors involved, problems for moose, exposure of northern populations of reindeer (Rangifer rangifer tarandus), and public health issues. Apparently, Lipoptena cervi was introduced into northeastern United States in the late 1800s, presumably on an unknown species of European deer, and it soon spread to white-tailed deer (Odocoileus virginianus). We review the current situation in Scandinavia and North America and document the first record of L. cervi on moose in northeastern United States.